New Advances on Fermentation Processes 2020
DOI: 10.5772/intechopen.89326
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria as Microbial Silage Additives: Current Status and Future Outlook

Abstract: Silage making is not a novel technique. However, the agricultural industry has made great strides in improving our understanding of-and efficiency in-producing high-quality silage for livestock. Silage microbiology research has been using the newest molecular techniques to study microbial diversity and metabolic changes. This chapter reviews important research that has laid the foundation for field-based utilization of silage inoculants. We also outline areas of current, and future, research that will improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 81 publications
2
0
0
Order By: Relevance
“…In the studies carried out by Nsereko et al (2008) and Ding et al (2019), it was reported that as it was known that LAB cannot degrade the polysaccharides that form the cell wall, in recent researches it was found that some special HetLAB strains such as L. buchneri, L. reuteri, L. crispatus, and L. brevis produced ferulate esterase, which could reduce the cell wall coverage, and this result was compatible with the result of our study that the lowest NDF content was in the HetLAB +2% molasses added group. Drouin et al (2019), in their study of alfalfa plant with Pediococcus pentosaceus and Lactobacillus plantarum inoculant, reported that they increased the breakdown of hemicellulose polysaccharides, one of the plant cell wall elements and this result supported the current study.…”
Section: Resultssupporting
confidence: 88%
“…In the studies carried out by Nsereko et al (2008) and Ding et al (2019), it was reported that as it was known that LAB cannot degrade the polysaccharides that form the cell wall, in recent researches it was found that some special HetLAB strains such as L. buchneri, L. reuteri, L. crispatus, and L. brevis produced ferulate esterase, which could reduce the cell wall coverage, and this result was compatible with the result of our study that the lowest NDF content was in the HetLAB +2% molasses added group. Drouin et al (2019), in their study of alfalfa plant with Pediococcus pentosaceus and Lactobacillus plantarum inoculant, reported that they increased the breakdown of hemicellulose polysaccharides, one of the plant cell wall elements and this result supported the current study.…”
Section: Resultssupporting
confidence: 88%
“…Additionally, Limosilactobacillus , which may be bacteria attached to the native grass itself, became the main bacteria guiding the fermentation in the CK group [ 67 ]. The differential bacteria in the LP, LB, and PB groups were Lactiplantibacillus , Lentilactobacillus , and Lactobacillaceae, which corresponded to the LAB added in each group, confirming that the use of LAB additives can change the main flora of silage fermentation, which is consistent with the studies of Chen et al [ 68 ] and Drouin et al [ 69 ].…”
Section: Discussionsupporting
confidence: 89%